Fidelity to participants when researching multilingual language teachers: A systematic review. Issue 1 (5th March 2022) - Calafato, Raees
Abstract: The research field of multilingualism in education has grown exponentially over the last two decades, with more and more studies published every year on the need for teachers to validate the whole linguistic repertoire of their students and help them draw on their multilingualism as a resource. What has, conversely, not been accorded sufficient attention by researchers is the multilingualism of the teachers tasked with realising this. This oversight, as it were, raises ethical issues for researchers that go beyond macro ethical considerations like the need to ensure participant anonymity, their protection from harm, and data confidentiality. Education is itself a complex, ethical enterprise, where engagement with teachers and students requires greater faithfulness, exactitude, and respect on the part of researchers. The need for such engagement, from an ethical standpoint, has been magnified as governments globally implement multilingual initiatives in schools and universities that encourage teachers to harness the growing linguistic and cultural diversity that surrounds them (and of which they are a part). Based on a systematic review of 59 published works between 2016 and 2021, this article discusses the importance of adopting a fidelity‐to‐participants approach when researching multilingual language teachers. Such an approach has been missing from most studies, yet it would benefit researchers and their participants, as well as policymakers and educators in several ways.